Generalized Hölder’s and Minkowski’s Inequalities for Jackson’s q-Integral and Some Applications to the Incomplete q-Gamma Function - Kwara Nantomah (Abstract and Applied Analysis)
We establish some generalized Hölder’s and Minkowski’s inequalities for Jackson’s q-integral. As applications, we derive some inequalities involving the incomplete q-Gamma function.